Knowledge of Residents and Barangay Officials on Disaster Risk Reduction and Preparedness in Oriental Mindoro, Philippines (American Journal of Multidisciplinary Research and Innovation, 2023)
This study assessed the level of disaster risk reduction knowledge of residents and barangay officials in the disaster-prone municipalities of Oriental Mindoro on disaster preparedness and significant differences on the assessment of the two groups of respondents. Guided by research questions, a structured questionnaire was prepared. The respondents of this study were the residents and the barangay officials including the chief of barangay tanods from the disaster-prone areas of the selected municipalities of the province of Oriental Mindoro. This study was conducted in the calamity-prone areas of Baco and Naujan municipalities. For the resident respondents, a total of 379 residents were selected from the total population of 24,550 in DPA1 and DPA2. On the other hand, total enumeration of the participants was applied in soliciting information from the 180 barangay officials including the chief of barangay tanods of the disaster-prone areas. To determine the respondents’ level of disaster risk reduction knowledge, weighted mean was used . To determine the significant differences in the assessment of the two groups of respondents, the one-way analysis of variance (ANOVA) and Scheffe test were used. Results revealed that barangay official and residents of the disaster-prone municipalities in Oriental Mindoro have a high level of disaster risk reduction knowledge signifying that the initiatives on information dissemination were effective. Moreover, there is a significant difference between the assessments of the residents and barangay officials on the extent of disaster risk reduction knowledge. barangay officials are more exposed to information because of their position.